Foto Bianchi: retratos e representações visuais do escolar (Ponta Grossa/PR, 1913-1943) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
It is understood that school photography goes beyond mere mimesis of reality, its production and uses carry a complexity of visual discourses and social functions that insert it in the field of representations and visualities. Therefore, it is a potential cultural artifact for historiographic problematization. Given such premises about the portrait produced in and for the school, the present paper aims to understand how the photographic representation of some school spaces in Ponta Grossa city was given by the Photo Bianchi studio's lens during its first photographers generation, comprehended between 1913-1943. The research uses the studio negative plates available at the Foto Bianchi Fund, located at the Paraná Memory House (Ponta Grossa), and some paper photographs available at the Campos Gerais Museum collection (Ponta Grossa). In addition, in order to contribute and support the analysis, a set of secondary sources are fundamental to the discussions: Paraná’s Public Instruction Regulation (1890), Paraná’s State Teaching Code (1917), Practical Handbook of Photographia (1925) and The Educational Bases of the Normal School (1927). Along with the sources of the period, the interviews of Rauly Bianchi (1982) and Raul Bianchi (2001) are essential to the problematic of some questions about the studio and its trajectory. Given this, the research is inserted in the History of Representations field, having as references Sandra Pesavento (2009), Roger Chartier (2010) and José Martins (2009). Also, it has the theoretical support of studies by Peter Burke and Boris Kossoy (2009; 2014) about the photography’s use as a historiographical document, Ulpiano Meneses (2003; 2005; 2012) and Raimundo Martins (2006) with their discussions about the Visual History and Visual Culture, André Rouillé (2009) and François Soulages (2005) regarding photographic statute and photographicity, Ana Maria Mauad (1996), Carvalho e Lima (1997) and Ivo Canabarro (2015) regarding a critical-analytical methodology against photographic documents. Finally, to support the school portrait’s notion, the researches of Rachel Abdala (2013) and Alik Wunder (2008) are used.
Keywords: Retratos escolares; Foto Bianchi; Representação Visual; School portraits; Foto Bianchi; Visual Representation; CNPQ::CIENCIAS HUMANAS::HISTORIA